2000
DOI: 10.1016/s0005-2736(00)00214-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the HIV-1 fusion peptide with large unilamellar vesicles and monolayers. A cryo-TEM and spectroscopic study

Abstract: We have examined the interaction of the human immunodeficiency virustype 1 fusion peptide (23 amino acid residues) and of a Trp-containing analog with vesicles composed of dioleoylphosphatidylcholine, dioleoylphosphatidylethanolamine and cholesterol (molar ratio, 1:1:1). Both the native and the Trp-substituted peptides bound the vesicles to the same extent and induced intervesicular lipid mixing with comparable efficiency. Infrared reflection-absorption spectroscopy data are compatible with the adoption by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
57
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 53 publications
5
57
1
Order By: Relevance
“…These studies not only confirm the predicted high affinity of MTRs for the membrane interface, but also support their role as promoters of lipid bilayer destabilization [12,13,34,[36][37][38]. In principle MTR-s might promote fusion by reducing the formation energies of the lipidic intermediates of fusion, and/or by accelerating the opening of fusion pores [39][40][41].…”
Section: Introduction: Membrane-transferring Regions Within the Glsupporting
confidence: 67%
See 1 more Smart Citation
“…These studies not only confirm the predicted high affinity of MTRs for the membrane interface, but also support their role as promoters of lipid bilayer destabilization [12,13,34,[36][37][38]. In principle MTR-s might promote fusion by reducing the formation energies of the lipidic intermediates of fusion, and/or by accelerating the opening of fusion pores [39][40][41].…”
Section: Introduction: Membrane-transferring Regions Within the Glsupporting
confidence: 67%
“…MTR partitioning into membranes has been quantitatively assessed in vesicular model systems using representative synthetic peptides [12,[29][30][31][32][33][34][35][36][37]. These studies not only confirm the predicted high affinity of MTRs for the membrane interface, but also support their role as promoters of lipid bilayer destabilization [12,13,34,[36][37][38].…”
Section: Introduction: Membrane-transferring Regions Within the Glmentioning
confidence: 76%
“…~8.5 Å from the bilayer center and ~10 Å from the lipid phosphorus. Infrared (IR) and solid-state NMR spectra of membrane-associated HFP suggested that the HFP-F8W had predominant β strand conformation under the conditions of the fluorescence experiments (16,27,36,37). In a different set of experiments, electron spin resonance spectra showed that chromium oxalate in the aqueous phase quenched the signal of membrane-associated HFP which was spin-labeled at M19 but did not quench HFP spin-labeled at A1 (30).…”
mentioning
confidence: 99%
“…HFP location in membranes has been primarily probed using a HFP-F8W mutant and by variation of the tryptophan fluorescence of this mutant with changes in environment (36,37). Key results have included: (1) fluorescence was higher for membrane-associated HFP-F8W than for HFP-F8W in buffered saline solution; (2) greater fluorescence quenching by acrylamide was observed for a soluble tryptophan analog than for membrane-associated HFP-F8W; and (3) similar fluorescence quenching of membrane-associated HFP-F8W was observed in samples containing either 1-palmitoyl-2-stearoyl-phosphocholine brominated at the 6, 7 carbons of the stearoyl chain or the corresponding lipid brominated at the 11, 12 carbons of the chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation